Dietary fibers with different viscosity regulate lipid metabolism via ampk pathway: roles of gut microbiota and short-chain fatty acid - Li, Yu; Xia, Daiyang; Chen, Jianying; Zhang, Xiufen; Wang, Heng; Huang, Liang; Shen, Jiajia; Wang, Shunxiang; Feng, Yan; He, Danyan; Wang, Jiaqing; Ye, Hui; et al. (Poultry science, 2022)
Dietary fiber (DF) improves gastrointestinal health and has important associations with the alleviation of intestinal diseases and metabolic syndrome. However, due to DFs complex characteristics, such as solubility, viscosity, and fermentability, the mechanism in these was not consistent. As an herbivore, the goose has a prominent digestive ability to DF. Therefore, we choose low, medium, and high viscosity DFs (respectively resistant starch-3 []RS], inulin [INU], and β–glucan [GLU]) as Magang goose diet treatment for 4 wk, to investigate the effect and potential mechanism of different viscosities DFs on the growth and development process of goose. In summary, three degrees of viscous DFs could decrease the mechanismic lipid level of geese by promoting acid-producing bacteria and short-chain fatty acid (SCFA) production, therefore, activating AMPK pathway-related genes through the gut-liver axis. High viscous DF has a greater lipid-lowering effect on geese, while medium viscous DF has preferable intestinal mucosal protection.